Cover Picture: Carcinogenic Organic Residual Compounds Readsorbed on Thermally Reduced Graphene Materials are Released at Low Temperature (Chem. Eur. J. 43/2013). Issue 43 (14th October 2013) - Ambrosi, Adriano; Wong, Gwendeline K. S.; Webster, Richard D.; Sofer, Zdeněk; Pumera, Martin
<x xml:space="preserve">Abstract</x> Carcinogenic organic residual compounds re‐adsorbed on thermally reduced graphene materials are released at low temperature. This is illustrated in the picture in which small organic carcinogenic compounds rain from graphene clouds on the hot surface of a desert (Canyonlands National Park, Utah). For more details see the Full Paper by M. Pumera et al. on page 14446 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>